(untitled) (قضايا سياسية, 2022)
The phenomenon of violent extremism is one of the entrances to the international, regional and local crises, especially those that were accompanied by changes in political regimes, or the growing popular resentment against the ruling authority. The phenomenon of extremism has emerged in the Middle East and has taken international dimensions, as if what happened with what is known as the Arab Spring revolutions is the official announcement of the emergence of the phenomenon of extremism in societies of change. What we live in today reminds us of previous historical stages, which many countries and societies have gone through in their various forms and levels. The phenomenon of extremism and extremism in it is an old phenomenon that arose and developed with the emergence and development of intellectual theory at the religious or ideological level, and the repercussions it has on the human lifestyle and its impact on the behavior of societies in general.